Visualisasi Nilai-nilai Islami melalui Media Video dalam Pembelajaran Akidah Akhlak di MA Al Manshuriyah Pagelaran - Muhammad Toha; Sriresnakamaliah Sriresnakamaliah; Nina Destiani; Muhammad Hubban Zen; Nazla Ramdhani Azzahra (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the use of video media in visualizing Islamic values in the teaching of Aqidah and Akhlak at MA Al Manshuriyah Pagelaran. The study is grounded in the need for a more contextual, engaging, and relevant learning approach for the digital generation, particularly in delivering concepts such as monotheism, proper conduct, and social morality. A descriptive quantitative method was employed involving 24 students using questionnaires and classroom observations. The findings indicate that video media enhances student engagement, clarifies the understanding of abstract concepts, and fosters a more interactive learning atmosphere. The visualization of Islamic values through video enables students to comprehend commendable behavior more concretely and in relation to their daily experiences. The study implies that video-based learning is an effective strategy to strengthen value internalization in Aqidah and Akhlak teaching and is recommended for continuous integration into instructional practices.